Advance care planning and pulmonary rehabilitation: participation and patient perspectives. Issue 2 (1st June 2012) - Nicholes, M; Burge, AT; Lee, A; Purcell, S; Miller, B; Norris, N; McArdle, S; Sandilands, S; Holland, AE
Abstract : Patients attending pulmonary rehabilitation generally have moderate to severe lung disease and are at increased risk for life threatening cardio-respiratory events. Enabling people with chronic lung disease to make informed choices about end of life care should be a high priority. However many health professionals are concerned about how to introduce advance care planning to these patients. The potential risk of upsetting patients and families and disengaging them from self management programs may be a barrier to the inclusion of advance care planning into standard care. In challenge to this assumption our study has shown that patients are receptive to ACP education delivered in a group setting by a non-medical professional in pulmonary rehabilitation and maintenance programs. Participants in PR&MP who attended a group ACP information session were invited to take part in semi-structured interviews regarding their experience and perceptions. Participants who chose not to attend the group ACP information sessions were also interviewed regarding the reasons for their choice. Iterative thematic analysis was undertaken. Major themes included the appropriateness of the setting; the key role of the educator; and that the session prompted discussion and action. No differences in themes between community and hospital settings were evident. Participants in this project strongly identified with the ACP educator, both in terms of modelling and illustration of the universal applicability of the concept. ACP was well accepted as part of a group education program within PR&MP, as assessed by a broad range of participants.